2018
DOI: 10.2478/ebtj-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence lifetime imaging of red yeast Cystofilobasidium capitatum during growth

Abstract: Red yeast Cystofilobasidium capitatum autofluorescence was studied by means of confocal laser scanning microscopy (CLSM) to reveal distribution of carotenoids inside the cells. Yeasts were cultivated in 2L fermentor on glucose medium at permanent light exposure and aeration. Samples were collected at different times for CLSM, gravimetric determination of biomass and HPLC determination of pigments. To compare FLIM (Fluorescence Lifetime Imaging Microscopy) images and coupled data (obtained by CLSM) with model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It has been previously shown that the C/N ratio is the key feature significantly affecting the accumulation of carbon-based intracellular metabolites (carbohydrates, lipids, pigments, etc.) [ 3 , 56 , 57 , 58 ]. Although there are many reports published on how C/N ratio influenced accumulation of lipids or carotenoids in Basidiomycetes yeast [ 3 , 7 ], the effect on β-glucan biosynthesis has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that the C/N ratio is the key feature significantly affecting the accumulation of carbon-based intracellular metabolites (carbohydrates, lipids, pigments, etc.) [ 3 , 56 , 57 , 58 ]. Although there are many reports published on how C/N ratio influenced accumulation of lipids or carotenoids in Basidiomycetes yeast [ 3 , 7 ], the effect on β-glucan biosynthesis has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…β-carotene and lutein have been shown to exhibit weak fluorescence with a peak near 520 nm when dissolved in hexane, while carotenoid-associated fluorescence in brain tissues had broad features with a maximum near 540 nm ( 70 ). Carotenoids with three distinct lifetimes of 0.03, 0.3, and 3.5 ns have been identified in yeast, where fluorescence lifetime was used to assess the abundance of different carotenoids on the basis of growth medium and phase ( 71 ). Mean autofluorescence of carotenoids such as lutein and zeaxanthin is in the range of 30–80 ps.…”
Section: Potential Contributions From Other Endogenous Fluorophoresmentioning
confidence: 99%